The Novel Internalins InlP1 and InlP4 and the Internalin-Like Protein InlP3 Enhance the Pathogenicity of Listeria monocytogenes - Harter, Eva; Lassnig, Caroline; Wagner, Eva Maria; Zaiser, Andreas; Wagner, Martin; Rychli, Kathrin (Frontiers in Microbiology, 2019)
The pathogenicity of the human foodborne pathogen Listeria (L.) monocytogenes relies on virulence factors such as internalins. In 2009/2010 two L. monocytogenes strains were responsible for a serious listeriosis outbreak in Austria, Germany and the Czech Republic. One of these clones, QOC1, which caused 14 cases including five fatalities, encodes the novel internalins inlP1, inlPq and inlP4 and the novel internalin-like protein inlP3 in the genomic region of hypervariable genetic hotspot 9 in addition to the standard set of virulence genes. The in silico prevalence study revealed that these genes rarely occur in L. monocytogenes and mainly in minor clonal complexes. To obtain first insights of the role of these genes in the pathogenicity of L. monocytogenes, we studied the gene expression under conditions mimicking the ingestion in the host. Expression of inlP1, inlP3, inlPq and inlP4 was increased under gastric stress and in intracellular bacteria grown in intestinal epithelial cells. Furthermore, colonization of the liver and the spleen was slightly, but significantly reduced 72 hours post infection in an oral mouse infection model when inlP1 or inlP4 was deleted. Moreover, the impact of InlP1 and InlP3 in virulence was shown in vitro in human intestinal epithelial cells. In this study we conclusively demonstrate a potential contribution of uncommon novel internalins and an internalin-like protein to the pathogenicity of L. monocytogenes.